Sustainable bromelain extraction from pineapple waste: ATPS purification, freeze-drying, and cosmetic safety evaluation - Ma. Rachel V. Parcon; Gladys Ann B. Bautista; Chelsea Kate F. Jose; Jan Anthony N. Ysulat; Geaver Nicolei C. Cortez; Andrea Nicole Y. Abarcar; Pauline Yarah H. Morales; John Cyrus O. Alfaro; Aileen C. Bidol (Acta Biochimica Indonesiana, 2026)
Background: Pineapple processing generates substantial waste; peels represent a rich source of bromelain, aproteolytic enzyme with dermatological applications. Objective: To develop sustainable bromelain extraction from pineapple peels using aqueous two-phase system(ATPS), evaluate freeze-dried extract, and assess safety for topical cosmetic use. Methods: Bromelain was extracted using PEG-4000/MgSO₄ ATPS and freeze-dried. Proteolytic activity was quantified by tyrosine release and gelatin digestion assays. Purified bromelain was incorporated into gel cleanser and serum formulations (2-5%, pH 4.5-7.0) and evaluated for physicochemical properties, microbial safety, and skin compatibility through human repeat insult patch testing (HRIPT). Results: The 10% PEG-4000/30% MgSO₄ system achieved optimal balance (37.64% yield, 2.80 U/mL activity). Freezedrying produced free-flowing powder. Formulations met ASEAN microbial limits (<1,000 cfu/g) and demonstrated non-irritating properties with low hypersensitivity risk in HRIPT. Conclusion: ATPS extraction combined with freeze-drying produces stable, bioactive bromelain suitable for safe